Synthesis of Palladium Nanoparticles by the Thermal Destruction of Pd(II) Solvate Complexes in Alcohols - Buryak, N.I.; Volkov, S.V. (Наносистеми, наноматеріали, нанотехнології, 2008)
The composition and structure of Pd(II) solvate complexes in alcohols within the temperature range of 20—150°C are investigated by spectroscopic methods.